At Risk in Rural America: Strategies for Educators - Kay Sather Bull; Marta Garrett (Educational Considerations, 1989)
There are many ways in which children and youth can become at-risk. This article presents a taxonomy of conditions that may contribute to students being "at risk" in rural areas.